2019
DOI: 10.1111/jace.16878
|View full text |Cite
|
Sign up to set email alerts
|

PLZST antiferroelectric ceramics with promising energy storage and discharge performance for high power applications

Abstract: Capacitors are widely used as energy storage elements in electric vehicles (EVs) and pulsed power. At present, it is still challenging to develop capacitor dielectrics with good energy storage and discharge performance. In this work, antiferroelectric (AFE) ceramics (Pb0.94La0.04)[(Zr0.6Sn0.4)0.92Ti0.08]O3 with enhanced antiferroelectricity were fabricated by a rolling process. The obtained ceramics have a high recoverable energy density of 5.2 J/cm3 and an extremely high efficiency of 91.2% at 327 kV/cm. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…(A) Temperature dependence of dielectric constant for PLZST‐1 ceramics, (B) Weibull distribution of BDS for PLZST‐4 ceramics, (C)‐(G) SEM images and grain size distributions for PLZST‐4 ceramics, (H) Comparison of W rec and η of AO1 and AT4 in this work with other reported ceramics, in which AO1 is (Pb 0.94 La 0.04 )(Zr 0.99 Ti 0.01 )O 3 in this work; AT4 is (Pb 0.94 La 0.04 )(Zr 0.49 Sn 0.5 Ti 0.01 )O 3 in this work; PBLZS is (Pb 0.91 Ba 0.045 La 0.03 )(Zr 0.6 Sn 0.4 )O 3 27 ; PLSZS is (Pb 0.94 La 0.02 Sr 0.04 )(Zr 0.9 Sn 0.1 ) 0.995 O 3 31 ; BNT‐ST is 0.75(Bi 0.58 Na 0.42 TiO 3 )‐0.25(SrTiO 3 ) 44 ; PLZST is (Pb 0.94 La 0.04 )[(Zr 0.6 Sn 0.4 ) 0.92 Ti 0.08 ]O 3 45 ; PSLZST is (Pb 0.955 Sr 0.015 La 0.02 )(Zr 0.75 Sn 0.195 Ti 0.055 )O 3 46 ; PLZST@SiO2 is Pb 0.97 La 0.02 (Zr 0.33 Sn 0.55 Ti 0.12 )O 3 @5 mol% SiO 2 47 ; BT‐BLT is 0.9BaTiO 3 ‐0.1Bi(Li 0.5 Ta 0.5 )O 3 48 ; PLZT‐M is (Pb 0.91 La 0.06 )(Zr 0.96 Ti 0.04 )O 3 ‐1 mol% MnCO 3 49 ; AN‐BM is AgNbO 3 ‐0.6 mol% BiMnO 3 50 ; STL/BNBT is (SrTiO 3 +Li 2 CO 3 )/(0.94Bi 0.54 Na 0.46 TiO 3 ‐0.06BaTiO 3 ) 51 ; BT‐BMZ is 0.85BaTiO 3 ‐0.15Bi(Mg 0.5 Zr 0.5 )O 3 52 ; PBLYST‐PLZST is (Pb 0.858 Ba 0.1 La 0.02 Y 0.008 )(Zr 0.65 Sn 0.3 Ti 0.05 )O 3 ‐(Pb 0.97 La 0.02 )(Zr 0.9 Sn 0.05 Ti 0.05 )O 3 53 ; ANT is Ag(Nb 0.85 Ta 0.15 )O 3 54 [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Discussionmentioning
confidence: 99%
“…(A) Temperature dependence of dielectric constant for PLZST‐1 ceramics, (B) Weibull distribution of BDS for PLZST‐4 ceramics, (C)‐(G) SEM images and grain size distributions for PLZST‐4 ceramics, (H) Comparison of W rec and η of AO1 and AT4 in this work with other reported ceramics, in which AO1 is (Pb 0.94 La 0.04 )(Zr 0.99 Ti 0.01 )O 3 in this work; AT4 is (Pb 0.94 La 0.04 )(Zr 0.49 Sn 0.5 Ti 0.01 )O 3 in this work; PBLZS is (Pb 0.91 Ba 0.045 La 0.03 )(Zr 0.6 Sn 0.4 )O 3 27 ; PLSZS is (Pb 0.94 La 0.02 Sr 0.04 )(Zr 0.9 Sn 0.1 ) 0.995 O 3 31 ; BNT‐ST is 0.75(Bi 0.58 Na 0.42 TiO 3 )‐0.25(SrTiO 3 ) 44 ; PLZST is (Pb 0.94 La 0.04 )[(Zr 0.6 Sn 0.4 ) 0.92 Ti 0.08 ]O 3 45 ; PSLZST is (Pb 0.955 Sr 0.015 La 0.02 )(Zr 0.75 Sn 0.195 Ti 0.055 )O 3 46 ; PLZST@SiO2 is Pb 0.97 La 0.02 (Zr 0.33 Sn 0.55 Ti 0.12 )O 3 @5 mol% SiO 2 47 ; BT‐BLT is 0.9BaTiO 3 ‐0.1Bi(Li 0.5 Ta 0.5 )O 3 48 ; PLZT‐M is (Pb 0.91 La 0.06 )(Zr 0.96 Ti 0.04 )O 3 ‐1 mol% MnCO 3 49 ; AN‐BM is AgNbO 3 ‐0.6 mol% BiMnO 3 50 ; STL/BNBT is (SrTiO 3 +Li 2 CO 3 )/(0.94Bi 0.54 Na 0.46 TiO 3 ‐0.06BaTiO 3 ) 51 ; BT‐BMZ is 0.85BaTiO 3 ‐0.15Bi(Mg 0.5 Zr 0.5 )O 3 52 ; PBLYST‐PLZST is (Pb 0.858 Ba 0.1 La 0.02 Y 0.008 )(Zr 0.65 Sn 0.3 Ti 0.05 )O 3 ‐(Pb 0.97 La 0.02 )(Zr 0.9 Sn 0.05 Ti 0.05 )O 3 53 ; ANT is Ag(Nb 0.85 Ta 0.15 )O 3 54 [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Discussionmentioning
confidence: 99%
“…The mixed powders were ball-milled in ethanol for 24 h, dried at 100 • C to remove moisture, and then calcined in an oven at 850 • C for 2 h. The calcined powders were converted into dense ceramic pellets via the rolling processing. 12,27 The ceramic pellets The crystal structure was determined by X-ray diffraction (XRD, D/Max2400, Rigaku Corporation) using Cu Ka radiation. The surface of each sample was observed by scanning electron microscopy (SEM, Quanta F250, FEI Quanta, FEI).…”
Section: Methodsmentioning
confidence: 99%
“…Based on this equation, the 𝑊 dis obtained was 0.36 and 0.49 J/cm 3 for PLZST and PLBZST, respectively. Meanwhile, as reported previously, 27 an alternative method exists for evaluating the energy storage performance via P-E loops. The recoverable energy density (𝑊 re ) can be calculated as…”
Section: 2mentioning
confidence: 95%
“…So often, the structure is INC for the best performing AFE compositions. [233][234][235][236][237][238][239][240][241][242][243] Chen et al have shown that the dynamic switching of the AFE double hysteresis loops of a given AFE follows a scaling law with the energy density having dependence on variables such as the amplitude of applied field and its frequency. 244,245 Temperature stable AgNbO 3 -based ceramics are usually fabricated by doping with Ta on the B site, which decreases the temperature of the M phase transitions.…”
Section: Afe Multilayer Ceramic Capacitorsmentioning
confidence: 99%
“…To facilitate charging and discharging of the AFE, a base material, such as PZT 95/5, is modified with additives, such as La and Ca, to minimize the hysteresis and suppress large volume changes that would create high field losses and induce microcracking. So often, the structure is INC for the best performing AFE compositions 233–243 . Chen et al have shown that the dynamic switching of the AFE double hysteresis loops of a given AFE follows a scaling law with the energy density having dependence on variables such as the amplitude of applied field and its frequency 244,245 …”
Section: Antiferroelectric Applicationsmentioning
confidence: 99%